Investing in Physical Assets and Economic Development: Perspectives on Sustainability - BK, Rabi Bahadur (Academia Journal of Humanities & Social Sciences, 2025)
This paper examines the investment practices in Nepal, focusing on the prevalent trend of investing in physical assets such as land and houses, and its implications for economic development. The study adopts a mixed-methods approach, combining exploratory and descriptive research designs. The primary data were collected through the semi-structured questionnaires from 18 households in Adarshabasti Tole Bikash Sanstha, Pokhara Metropolitan City-18, Kaski District. The findings of the study reveal that most households prefer investing in physical property due to the factors such as potential price appreciation, social pressures, and cultural influences. However, the barriers such as market uncertainty, political instability, limited financing options, and high property costs hinder investment in more productive sectors like business and trade. While there is a strong preference for business investment across the different caste groups, the concerns about government support and financial risks deter an active involvement in the entrepreneurial ventures. The study highlights a complex relationship between the property markets and business investment. The paper concludes that addressing the barriers to business investment and reducing the market uncertainties can encourage more diversified investment practices, leading to the sustainable economic growth. This study contributes to the field of development studies by examining how the traditional investment practices in physical assets impact a long-term economic development in Nepal.